Midwifery students’ experiences: Violations of dignity during childbirth - Haseli, Arezoo (Nursing ethics, 2024)
BackgroundThe principle of human dignity is woven into the ethical principles of the midwifery profession, noted as both an obligation and a human right.Research ObjectivesThe aim of this study is to explore the experiences of midwifery students regarding threats to women's dignity during childbirth.Research DesignThis is a qualitative study with explorative design. Participants and Research Context: The research was carried out in 2022 at Kermanshah University of Medical Sciences, involving 32 midwifery students in individual interviews that lasted between 30 and 90 minutes. These participants aged 21 to 28 years, with an average age of 23.5 years, provided their perspectives on the matter.ResultsFour key themes described the threats to women’s dignity during childbirth: 1) professional incompetence, 2) abuse of power imbalance, 3) caring only for physical and not mental health, and 4) structural issues within the healthcare system. Professional incompetence was characterized by outdated practices and lack of adherence to evidence-based medicine. Abuse of power imbalance was demonstrated in instances where the authoritative position of healthcare providers was misused, thereby disrupting the respectful care that women are entitled to receive. The disproportionate emphasis on physical health over mental health was evidenced by the disregard for mothers' psychological well-being during childbirth. Lastly, systemic structural issues emerged as significant impediments, revealing the need for system-wide changes. Ethical considerations: This study was approved by the Ethics Committee of the Research Deputy at Kermanshah University. Participation was voluntary and the confidentiality were maintained.ConclusionThe findings underscore the role that unprofessional behavior, ethical lapses in medical practices, and systemic challenges play in undermining maternal dignity during childbirth. These threats necessitate urgent attention and must be adequately addressed in policy development and program implementation to safeguard the dignity of mothers during childbirth.